Leadership Model in the Management of Public Service Agency State University - Sengkey, Marssel Michael; Lumapow, Harol R.; Lengkong, Jeffry S. J.; Pangalila, Theodorus (International Journal of Information Technology and Education, 2024)
The aim of this research is to describe the leadership model in managing the Public Service Agency and the factors that hinder and support leadership in the management of the Public Service Agency at Universitas Negeri Manado (Unima). This research uses a descriptive qualitative approach, in the form of research with a case study method or approach (Case Study) with 5 research subjects. The research results show that the leadership model used in managing the status of Public Service Agency State Universities is the Mapalus leadership model. The name Mapalus is used based on similarities with Unima's vision, namely Superior and Innovative Unima based on Mapalus. The mapalus leadership model is a leadership approach that prioritizes collaboration, open communication, and synergy between leaders and team members. In this model, leaders not only command from above, but also work together with team members to achieve common goals. Leaders with this leadership model build strong relationships with team members, understand their needs and potential, empower them to achieve optimal performance, and encourage active participation in decision making and create a positive and inclusive work environment. Factors that hinder leadership in managing the Public Service Agency at Unima include resistance of team members and staff to change, lack of understanding of the implications of change, uncertainty regarding changes in status, lack of support from stakeholders, resistance to existing organizational culture and lack of resources or facilities. adequate. On the other hand, factors that support leadership include open and effective communication, understanding a clear vision, involving team members and stakeholders in planning and implementation, organizational culture that supports collaboration and innovation, developing new leadership skills through training and collaboration, ensuring decisions and actions reflecting stakeholder expectations and needs, support from internal and external parties, evaluating the impact of policies and decisions through collecting feedback and analyzing performance data, effective communication in overcoming resistance to change and constructive conflict management.